Incidence of subclinical atherosclerosis as a marker of cardiovascular risk in retired professional football players - Hurst, R. T.; Burke, R. F.; Wissner, E.; Roberts, A.; Kendall, C. B.; Lester, S. J.; Somers, V.; Goldman, M. E.; Wu, Q.; Khandheria, B. (The American Journal of Cardiology, 2010)
The purpose of this study was to evaluate subclinical atherosclerosis in retired professional football players. Two hundred one healthy former professional football players (mean age 50.8 years; mean body mass index 31.5 kg/m2) were screened for the prevalence of cardiovascular risk factors, metabolic syndrome, and subclinical atherosclerosis by carotid artery ultrasound and compared with a cohort of men of similar body mass index referred for the assessment of subclinical atherosclerosis by carotid ultrasound. The prevalence of carotid artery plaque in the players was not significantly different from that of the body mass index-matched patients (33.3% vs 29.3%, p = 0.45). For the 2 groups, the prevalence of carotid artery plaque was >3 times higher than that reported in general population studies of patients with the same age range, gender, and exclusions. Metabolic syndrome prevalence was higher in linemen than in nonlinemen (45.8% vs 22.5%, p = 0.001), but there was no statistical difference in plaque presence between linemen and nonlinemen (27.1% vs 35.9%, p = 0.23). In conclusion, despite their elite athletic histories, former professional football players have a similar prevalence of advanced subclinical atherosclerosis as a clinically referred population of overweight and obese men.